Renewable and Sustainable Materials in Green Technology - Yhaya, Mohd Firdaus (SpringerBriefs in Applied Sciences and Technology,, 2018)
This book discusses recent developments in renewable and sustainable materials from a green technology perspective and how these materials interact with the environment. It highlights the fundamental processes involved in the production of renewable and sustainable materials, including chemical and biological approaches as well as these materials' potential application as green technological option. Written in a didactic style, it offers a guide and insights into renewable and sustainable materials. Each chapter provides in-depth technical information on the material's theory and its applications. The book shows how new materials may help us solve human and environmental issues in the future and suggests where current research may lead.